(untitled) (Perner’s Contacts, 2022)
The toll road service is planned and built to fund road construction and management of traffic operations. Although the toll service has several benefits, it also has challenges by creating a queue in the event of high traffic. Queues at a toll service in addition to pollution and waiting time costs also expose drivers to road traffic accidents and affect the economy of the country. Queuing problems at highway gates and exits due to toll service have become the main concern for transport managers and planners because of the randomness of inter-arrival and service time. The critical point in the management of toll road services is finding the optimal number of servers. This paper aims to analyze the queue feature to optimize the toll service using analytical and simulation models by considering the Addis-Adama expressway toll service in Ethiopia. The paper used a mathematical model and a simulation model using the CPN tools to investigate the queuing parameters. Then the model results helped us to get the optimum output by using economic analysis and identifying the minimum waiting time and operating cost without expense. The performance of the toll service highly depends on the number of servers, the number of vehicles in the system and queue, waiting time in the queue, service time, and inter-arrival time.